FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN PROGRAM TOTAL QUALITY CONTROL (TQC) PADA PEGAWAI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN ROKAN HULU - KURNIAWAN, TRI PUJI (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
Tri puji kurniawan. Nim 1125028. In 2015.Faktor-Factors Affecting Implementation of the Program of Total Quality Control (TQC) In Office Employee Disaster Management Agency Rokan Hulu. Main supervisor: Heffi Christya Rahayu, SE.MSi and Second Counselor: Hidayat, SE, MM. This study aims to determine the factors that affect the implementation of the program of Total Quality Control (TQC) office employees of the district disaster management agency rokan hulu. The method in this research is the method of observation, and questionnaire, the study was conducted in June-August 2015. The sampling technique using saturated sampling of 62 people, an instrument in this research is to test the validity and reliability test, descriptive data analysis techniques kuantitataif. Results of the study respondents about the level of achievement factor disagreement very good category (90.1%), the factor used by the head pretty good category (71.6%), the factor is not interest in running the program is very good category (92%), the factor additional burden categorized as excellent (89.6%), in the category of envy factor for unfavorable attitude (68.7%), and in the absence of factor group time categorized quite good (77%). Keywords: Total Quality Control